The Role of Social Environment in Employee Work Motivation: A Case of X Public Company at Jatiluhur Dam - Isnajati, Louisiani Mansoni; Anugerah Pratama, Yudhistira (International Journal of Digital Marketing Science, 2025)
Employees need motivation to do their jobs well, so companies, institutions, or organizations need to create a good working atmosphere so that employees are self-motivated. Therefore, it should be understood that the motivation possessed by employees has the potential to improve the quality of their work. Work motivation can be reviewed based on the social environment consisting of family, workmates, peers, and society. This study aims to analyze the four dimensions of the social environment of X Public Company's employees. This study used a combined method with a concurrent nested design. Determination of the number of subjects using a census, meaning that all employees at X Public Company were taken as respondents, which was as many as 135 people. The data collection techniques used were interviews and secondary data. The results show that the social environment of X Public Company's employees has implemented its role well, as seen from the total score of 6,057. However, society environment has not supported optimally, so this is still an obstacle in the motivation of X Public Company's employees. In this case, not only for employees, but X Public Company also needs to play a role in maintaining employee work motivation, because employee work motivation can also provide a positive image and maintain the sustainability of X Public Company's operations.